Acculturation of Islam and Javanese Culture in Public Servant Ethics - Mu’adi, Sholih; Sofwani, Ahmad (el Harakah: Jurnal Budaya Islam, 2018)
The acculturation of Islam and Javanese culture has occurred since the golden age of Islamic kingdoms in Java. Islamic boarding school (pesantren) has been developing widely during the age of Demak and Mataram kingdoms. This development is a product of acculturation between Islamic and Hindu education systems. Islamic boarding school during the heyday of Islamic kingdoms is the institution of education designed to develop and produce royal bureaucrats or nobility officials who understand both Islam ethic and Javanese culture. In recent days, Islamic boarding school has successfully produced leaders who are not only religious as Moslem but also fostering Javanese culture. The leader is a role-model for the followers. Leader behavior is the most central issue in the eye of followers. Therefore, the leader is always required to show good attitudes and positive values, and both virtues can be evolved from the understanding of religion and culture (especially Javanese culture). In accord with Javanese philosophy, human life perfection is understood in term of a totality involving creation (cipta), sense (rasa), and wish (karsa). This totality gives a description that public servant ethics cannot escape from the effect of Islam religion and Javanese culture. Akulturasi budaya Islam dan Jawa telah terjadi sejak zaman keemasan kerajaan Islam di Jawa. Pesantren telah berkembang secara luas pada zaman kerajaan Demak dan Mataram. Perkembangan ini merupakan produk akulturasi antara sistem pendidikan Islam dan Hindu. Pondok pesantren selama masa kejayaan kerajaan Islam menjadi lembaga pendidikan yang dirancang untuk mengembangkan dan menghasilkan birokrat kerajaan atau pejabat bangsawan yang memahami etika Islam dan budaya Jawa. Kini pesantren telah berhasil menghasilkan pemimpin yang tidak hanya beragama Islam tetapi juga membina budaya Jawa. Pemimpin adalah teladan bagi para pengikut. Perilaku pemimpin termasuk hal utama di mata pengikut. Oleh karena itu, pemimpin selalu dituntut untuk menunjukkan sikap yang baik dan nilai-nilai positif, dan kedua kebajikan tersebut dapat berevolusi dari pemahaman agama dan budaya (khususnya budaya Jawa). Sesuai dengan filsafat Jawa, kesempurnaan hidup manusia dipahami dalam arti totalitas yang melibatkan penciptaan (cipta), rasa (rasa), dan harapan (karsa). Totalitas ini memberikan gambaran bahwa etika pegawai negeri tidak bisa lepas dari pengaruh agama Islam dan budaya Jawa.